2008
DOI: 10.1002/bit.21991
|View full text |Cite
|
Sign up to set email alerts
|

Development of a stable dual cell‐line GFP expression system to study estrogenic endocrine disruptors

Abstract: Environmental estrogenic endocrine disruptors are a health concern. Here we constructed a dual cell-line green fluorescence protein (GFP) expression system to identify and study endocrine disrupting compounds with activities of estrogen receptor agonists or antagonists. Human breast cancer MCF-7 cells and endometrial carcinoma Ishikawa cells were infected with a two tandem estrogen response elements--E4 promoter-GFP reporter gene construct. The use of GFP reporter enabled direct and simple evaluations of cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…TAM and RAL acted as estrogenic agonists and generated significant estrogenic responses in Ishikawa-GFP cells. Data suggested TAM and RAL stimulatory effects on ERERE-mediated gene transcriptions in Ishikawa cells (Xu et al, 2008). Flamini et al (2009) reported that TAM activates an ER/Ga13/RhoA/ROCK/moesin signaling pathway in Ishikawa cells and in primary cultured stromal cells.…”
Section: Williams-brown Et Al (2011) Used the Nonmalignant Immortalimentioning
confidence: 99%
See 1 more Smart Citation
“…TAM and RAL acted as estrogenic agonists and generated significant estrogenic responses in Ishikawa-GFP cells. Data suggested TAM and RAL stimulatory effects on ERERE-mediated gene transcriptions in Ishikawa cells (Xu et al, 2008). Flamini et al (2009) reported that TAM activates an ER/Ga13/RhoA/ROCK/moesin signaling pathway in Ishikawa cells and in primary cultured stromal cells.…”
Section: Williams-brown Et Al (2011) Used the Nonmalignant Immortalimentioning
confidence: 99%
“…E2 increased VEGF gene transcription and protein secretion, but RAL did not influence the level of VEGF (Dai et al, 2009). Xu et al (2008) used TAM and RAL to treat human breast cancer MCF7 cells and Ishikawa cells that were infected with a two tandem estrogenic response element (E4 promoter-GFP reporter gene construct). TAM and RAL acted as estrogenic agonists and generated significant estrogenic responses in Ishikawa-GFP cells.…”
Section: Williams-brown Et Al (2011) Used the Nonmalignant Immortalimentioning
confidence: 99%
“…18,19,21,22 Advances in genetic manipulation technology, particularly using stem cells, 23 also holds exciting possibilities for 'body-on-achip' devices because uorescent reporters bound to promoters for specic biochemical markers can be used to study whether drug treatment causes alterations in phenotypic expression patterns. 24 Integration of microelectrode arrays into multi-organ devices provides the means to drastically increase the analytical power of such systems. Measurement of the electrophysiological properties of cell types such as neurons, cardiomyocytes and skeletal muscle permits direct functional assessment of these cells in real time.…”
Section: Multi-organ In Vitro Modelsmentioning
confidence: 99%
“…[6,8,9] for examples). Optical measurements have also been made of glutathione levels [6,10,11], uptake of a drug [8], and expression levels of protein using green fluorescent protein (GFP) [18]. In other systems, electrical measurements have been used [3,[19][20][21] in combination with optical measurements.…”
Section: Advantages and Challenges Of μCcasmentioning
confidence: 99%